2020
DOI: 10.4314/agrosh.v20i1.5s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of walnut on the nutritional and physicochemical properties of biscuits made from whole wheat

Abstract: In this study, the influence of walnut flour in biscuit production was studied. Biscuits were made from blends of whole wheat with walnut flours and were assessed for quality attributes and storability. Walnut was blended with whole-wheat thus: B (2%:98%); C (4%:96%); D (6%:94%); E (8%:92%) and F (10%:90%), while plain whole wheat flour served as control (Sample A). The biscuits were baked in the oven operated at 1800C for 20-30 minutes, cooled, packaged, stored for eight weeks, and analysed for physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Assessment of the protein content with respect to supporting growth and tissue maintenance highlights its potential use as alternative protein source in infant formulations. The fortification of wheat flour with African walnut flour for baking of various pastries (biscuits) indicated improved essential amino acid composition and lower microbial load of the final product when compared with the control (wheat flour biscuit only), even after storage of up to 8 weeks (Dauda et al, 2020). This is because African walnut flour is one of the oilseeds that contain all the essential amino acids necessary for various biochemical activities in man, particularly in protein synthesis (Tchiegang et al, 2001;Asaolu, 2009).…”
Section: Nutritional Composition and Potential To Improve Nutrition A...mentioning
confidence: 99%
See 3 more Smart Citations
“…Assessment of the protein content with respect to supporting growth and tissue maintenance highlights its potential use as alternative protein source in infant formulations. The fortification of wheat flour with African walnut flour for baking of various pastries (biscuits) indicated improved essential amino acid composition and lower microbial load of the final product when compared with the control (wheat flour biscuit only), even after storage of up to 8 weeks (Dauda et al, 2020). This is because African walnut flour is one of the oilseeds that contain all the essential amino acids necessary for various biochemical activities in man, particularly in protein synthesis (Tchiegang et al, 2001;Asaolu, 2009).…”
Section: Nutritional Composition and Potential To Improve Nutrition A...mentioning
confidence: 99%
“…These are valuable fundamental food forms that can be combined in various proportions with other condiments to produce nutrient-rich cooked or baked products such as pastriesbiscuits, cookies, bread, etc. (Ndie et al, 2010;Awofadeju, 2020;Dauda et al, 2020;Awofadeju et al, 2021). Studies have reported favorably on the physicochemical characteristics of the African walnut flour, which has been applied in combination with wheat flour for baking of cookies, buns, and bread (Dauda et al, 2020).…”
Section: Nutritional Composition and Potential To Improve Nutrition A...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is known in Eastern Nigeria as Ukpa (Igbo), Western Nigeria as "Awusa or Asala" (Yoruba), "Okhue or Okwe" (Edo) (Ayoola et al, 2011). Tetracarpidium conophorum is a climbing shrub of about 10-20ft long, it is normally planted under an indigenous tree so that can provide strong support for the heavy weight of the climber when fully established on the crown of the tree, and in some cases where they cannot be harvested manually; they are left till full maturation after which the pods fall off and are picked, removed from the rotten pods, washed and sold in the market (Dauda et al, 2020). The objective of isolation and characterization of the bioactive component of Tetracarpidium conophorum in disolvent methanol is to extract some chemicals from the Tetracarpidium conophorum seed, this extraction of the chemical act as: antioxidants, anticancer, antimicrobial property.…”
Section: Introductionmentioning
confidence: 99%